Tailored Plum Pudding‐Like Co2P/Sn Encapsulated with Carbon Nanobox Shell as Superior Anode Materials for High‐Performance Sodium‐Ion Capacitors. Issue 16 (27th February 2019) - Ren, Xiaochuan; Ren, Zhiguo; Li, Qingwei; Wen, Wen; Li, Xiaofang; Chen, Ye; Xie, Lei; Zhang, Liao; Zhu, Daming; Gao, Biao; Chu, Paul K.; Huo, Kaifu
Abstract: Sodium‐ion capacitors (SICs) are emerging energy storage devices with high energy, high power, and durable life. Sn is a promising anode material for lithium storage, but the poor conductivity of the a‐NaSn phase upon sodaition hinders its implementation in SICs. Herein, a superior Sn‐based anode material consisting of plum pudding‐like Co2 P/Sn yolk encapsulated with nitrogen‐doped carbon nanobox (Co2 P/Sn@NC) for high‐performance SICs is reported. The 8–10 nm metallic nanoparticles produced in situ are uniformly dispersed in the amorphous Sn matrix serving as conductive fillers to facilitate electron transfer in spite of the formation of electrically resistive a‐NaSn phase during cycling. Meanwhile, the carbon shell buffers the large expansion of active Sn and provides a stable electrode–electrolyte interface. Owing to these merits, the yolk–shell Co2 P/Sn@NC demonstrates a large capacity of 394 mA h g −1 at 100 mA g −1, high rate capability of 168 mA h g −1 at 5000 mA g −1, and excellent cyclability with 87% capacity retention after 10 000 cycles. By integrating the Co2 P/Sn@NC anode with a peanut shell‐derived carbon cathode in the SIC, high energy densities of 112.3 and 43.7 Wh kg −1 at power densities of 100 and 10 000 W kg −1 are achieved. Abstract : A novel yolk‐like nanobox consisting of the plum pudding‐like Co2 P/Sn yolk and nitrogen‐doped carbon shell is designed and fabricated controllably as superior anode materials for sodium‐ion capacitor and the uniformly distributed metal nanoparticles serving as conductive fillers to maintain the high conductivity facilitating electron transfer in spite of the formation of electrically resistive a‐NaSn during cycling.